Dielectric response features and oxygen migration on rare earth modified lead titanate ferroelectric ceramics - Pelaiz-Barranco, A.; Guerra, J. D. S. [UNESP]; Calderon-Pinar, F.; Arago, C.; Garcia-Zaldivar, O.; Lopez-Noda, R.; Gonzalo, J. A.; Eiras, J. A. (Springer, 2009)
Rare earth (RE) and manganese-modified lead titanate ceramics were studied concerning the presence of two peaks in the temperature dependence of the dielectric permittivity. An eventual incorporation of the RE into A-site and/or B-site in the perovskite structure and the oxygen migration were considered as causes of the observed phenomenon. The structural analysis showed that at least a small amount of Ti(4+) could be substituted by the RE ions. It was considered from the pyroelectric and electrical conductivity results that, even when an eventual incorporation of the RE into the A-site and/or B-site of the structure could be possible, both peaks could not be associated with paraelectric-ferroelectric (PE-FE) phase transitions. The observed peak at lower temperatures has been associated with the PE-FE phase transitions, whereas the hopping of oxygen vacancies has been considered as the cause for the dielectric anomaly observed at higher temperatures.